Bagaimana Peran Istri Dalam Mencapai Maqashid Syariah: Istri Sebagai Manajer Keuangan - Inggriani, Lutfia; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this study was to determine the form of the implementation of householdÂ financial management in achieving maqashid sharia. This study using qualitative approachÂ explanatory case studies. The data was collected by interview, observation andÂ documentation of the research object which is the member of IWAPI Surabaya.The results obtained are of religious knowledge that has an impact on the behavior of theÂ members of IWAPI Surabaya in managing household finances based on sharia. While theÂ business skills âlessâ have a strong impact on the financial management of daily household.Â The whole informants generally know the rules of religion in achieving Maqashid Al-ShariâahÂ and make the wealth as a support in meeting the needs of religion and the world. With aÂ good understanding of religion owned, the members of IWAPI Surabaya is able to implementÂ it into the form of maintenance of religion, life, intellect, lineage and property according toÂ religious teachings.